Overview of Cybersecurity Challenges in Fourth Industrial Revolution - Abdulrahman Abdullah Alghamdi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The fourth industrial revolution (4iR) is known as Industry 4.0 and it is considered the age of innovative technologies such as mobile, social media, cloud, Internet of things (IoT), and Artificial intelligence (AI). This revolution involves a hyper connected system that includes the Internet of things and cloud computing technologies in smarter use of computers. IoT is a new standard of adopting sensors and actuators equipped within the objects for establishing an effective computing environment. With the applications of all these technological systems, cybersecurity plays an imperative role in the rise of this fourth industrial revolution security in the field of Internet of Things, Blockchain and the Artificial Intelligence. Cyber threats in the IoT such as Lack of Security and Privacy, Vulnerable to web interfaces, Vulnerable Web Interfaces and Default weak and hard coded credentials were analyzed. This research also identifies the various Cyber threats and presents a structured analysis of the most frequently adopted security applications for these attacks.